내반 슬관절 환자의 슬관절 전치환술에서 인대 균형 시 천부 내측측부인대의 골막하 거상술 및 다발 자침 천공술의 비교 - 이기원(KiWon Lee); 최영준(Young-Joon Choi,); 배주열(Joo-Yul Bae); 조성윤(Sungyoon Cho); 안태환(Taehwan Ahn) (The journal of the Korean Orthopaedic Association, 2024)
목적: 내반 슬관절 골관절염 환자의 슬관절 전치환술에서 내측 연부조직의 이완은 적절한 균형을 얻기 위해 필수적이다. 본 연구에서는 천부 내측측부인대 유리술에서의 골막하 거상술과 다발 자침 천공술을 비교하여, 다발 자침 천공술의 유용성 및 안전성을평가하고자 하였다. 대상 및 방법: 2018년 4월부터 2020년 4월까지 내반 슬관절로 양측에 일차 슬관절 전치환술 및 천부 내측측부인대 이완술을 시행받은 환자들 중 한 쪽은 골막하 거상술, 반대쪽은 다발 자침 천공술을 시행받은 152명의 환자를 대상으로 후향적으로 분석하였다. 골막하 거상술에서는 곡선형 절골기를 이용하여 경골 근위부에서 천부 내측측부인대 전방부에 거상술을 시행하였고, 다발 자침천공술에서 18 Gauge 척추 바늘을 이용하여 천부 내측측부인대의 천공을 시행하였다. 후속 굴곡, 굴곡 구축, 관절가동범위를 포함하는 임상 결과와 미국슬관절학회(Knee Society, KS) 점수를 비교 분석하였고, 천부 내측측부인대의 과도한 이완을 포함하는수술 관련 합병증을 평가하였다. 결과: 골막하 거상술군과 다발 자침 천공술군에서 술 전 변형(내반 4.22° vs. 3.76°), 미국슬관절학회 점수(31.05 vs. 31.78), 후속굴곡(125.86° vs. 126.48°), 굴곡 구축(6.09° vs. 5.69°) 및 관절운동범위(119.77° vs. 120.79°)는 차이가 없었다. 술 후 1년째 추시에서, 두 군 간의 미국슬관절학회 점수(93.01 vs. 92.64), 후속 굴곡(134.24° vs. 134.64°), 굴곡 구축(0.36° vs. 0.49°) 및 관절운동범위(133.88° vs. 134.14°)에서 유의한 차이가 없었고(p=0.662, 0.749, 0.493, 0.835), 수술 후 통증 호소정도(58명 vs. 66명) 및미국슬관절학회 통증 점수(43.31 vs. 43.04)에 대해서 두 군 간의 통계적인 차이는 없었다(p=0.473, 0.745). 골막하 거상술군에서는 5예에서 과도한 이완이 발생하여 다발 자침 천공술군과 비교하여 유의미한 차이가 있었으나(p=0.024), 추적관찰상 내측 불안정성으로 진행하지는 않았다. 결론: 다발 자침 천공술은 통제 가능한 이완이 가능하며 기존의 골막하 거상술을 이용한 수술 방법과 더불어 성공적인 인대 균형을 위한 하나의 선택지가 될 수 있을 것이라 생각한다 Purpose: Medial soft tissue release in knee varus deformities during total knee arthroplasty (TKA) is necessary for adequate gap balancing. This study compared the clinical outcomes and complications of subperiosteal elevation (SE) and multiple needle puncturing (MNP) for superficial medial collateral ligament (sMCL) release and evaluated the effectiveness and safety of MNP. Materials and Methods: This study retrospectively analyzed 152 patients who underwent both TKA and sMCL release for degenerative osteoarthritis with varus alignment; one knee from each patient underwent SE and the other underwent MNP between April 2018 and April 2020. In SE, subperiosteal release was performed on the proximal tibia of the anterior portion of the sMCL using a curved osteotome. For MNP, an 18-gauge needle was used to puncture the sMCL. The clinical outcomes, including knee further flexion (FF), flexion contracture (FC), range of motion (ROM) and Knee Society (KS) scores, were compared. Surgical complications, including sMCL overrelease, were also evaluated. Results: For the SE and MNP groups, the preoperative KS scores (31.05 vs. 31.78), knee alignment (varus angle, 4.22° vs. 3.76°), FF (125.86° vs. 126.48°), FC (6.09° vs. 5.69°) and ROM (119.77° vs. 120.79°) did not differ preoperatively. At one-year follow-up, postoperative KS scores, FF, FC and ROM were similar in the two groups (93.01 vs. 92.64 points; 134.24° vs. 134.64°; 0.36° vs. 0.49°; 133.88° vs. 134.14°; p=0.662, 0.749, 0.493 and 0.835 respectively), and no statistically significant differences in terms of postoperative pain and KS pain score were observed between the two groups (66 vs. 58 patients and 43.31 vs. 43.04 points; p=0.473 and 0.745, respectively). In the SE group, five cases showed intraoperative over-release of the sMCL and a significant difference from the MNP group (p=0.024) but showed no medial instability at the final follow-up. Conclusion: Compared with the SE technique, MNP showed no significant difference in the clinical outcomes and fewer complications, such as over-release of the sMCL, and could be a safer alternative to achieve a balanced TKA. KCI Citation Count: 0